Self-Care Ability of Patients With Severe Mental Disorders: Based on Community Patients Investigation in Beijing, China - Chen, Chen; Chen, Yun; Huang, Qingzhi; Yan, Shengming; Zhu, Junli (Frontiers in Public Health, 2022)
Background Severe Mental Disorders have become a topic of increasing interest in research due to their serious consequences for the quality of life and functioning. In the pages that follow, it will be argued that the self-care ability and its influencing factors among patients with severe mental disorders in Beijing, according to the questionnaire survey in 2019. Methods Proportionate stratified sampling was used to select representative patients as samples. The demographic characteristics of were obtained from the Management Information System for Severe Mental Disorders and the questionnaires. The self-care ability was measured by self-made scales. Descriptive statistics, t-test, and multiple linear regression were used to analyze the data. Results We surveyed 662 people and found that the deficiency of self-care ability is common in patients with severe mental disorders. Self-care ability was positively correlated with educated levels and guardian takes care of alone, and negatively correlated with age, course of disease and physical disease (P < 0.05). From a dimensional perspective, the daily basic activity was positively correlated with educated levels and negatively correlated with physical disease (P < 0.05); the housework ability was positively correlated with gender, educated levels and medication adherence, and negatively correlated with source of income and physical disease (P < 0.05); the social function was positively correlated with educated levels, guardian takes care of alone and medication adherence, and negatively correlated with age, source of income, course of disease and physical disease (P < 0.05). Conclusion The self-care ability of patients with severe mental disorders is affected by many factors, including patient characteristics and social factors. Therefore, targeted interventions are needed to help patients restore their self-care ability, which requires the joint efforts of the government and the whole society.